The English East India Company and Cochinchina (1614–1705): from free trade to coercion. (3rd July 2021) - Tran, Ngoc Dung
ABSTRACT: By investigating English primary materials kept in the India Office Records, this study reviews relations between the English East India Company and Cochinchina (1614–1705) to argue that the Company changed its connecting strategy towards Cochinchina from commercial and diplomatic approaches to more aggressive methods. Cochinchina witnessed these strategic changes by the Company during its first century: the English embarked on commercial voyages to the kingdom in the 1610s, exploited a diplomatic approach in the mission 1695–1696 and forcefully built a military fortification in the period 1702–1705. Rather than re-narrating the English presence in Cochinchina, this article considers it as a case study to research the Company's transformation process, as they not only sought to trade with this market but also recognized and exploited its geopolitical potential. Moreover, the study analyses the Cochinchinese Court's skilful diplomatic responses to the English, in order to provide a comprehensive view of these relations, and fully explore the reasons for the failures of the English in settling a fortification in Cochinchina, and in their efforts at trade and diplomacy in the 1610s.